2016
DOI: 10.1016/j.molonc.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical WNT5A signaling up‐regulates the expression of the tumor suppressor 15‐PGDH and induces differentiation of colon cancer cells

Abstract: The tumor suppressor 15-hydroxyprostaglandin dehydrogenase (15-PGDH) is the key enzyme in prostaglandin E catabolism and is down-regulated in colorectal cancer (CRC) tissue. Canonical Wnt signaling is frequently elevated in colon cancers and has been shown to down-regulate 15-PGDH expression. Therefore, we have in the current study investigated if the non-canonical ligand WNT5A relates to increased expression of 15-PGDH in colon cancer cells. In the same cohort of patients, we demonstrated a parallel and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…We observed significantly lower CysLT 2 staining in the tumor tissue compared with the corresponding normal tissue from the same patient. In a recent study, these paired samples were also stained with a 15-PGDH-specific antibody, and the normal colon samples showed significantly higher 15-PGDH protein expression compared to the matched colon cancer samples [21]. These findings are in good agreement with our mRNA data.…”
Section: Resultssupporting
confidence: 90%
“…We observed significantly lower CysLT 2 staining in the tumor tissue compared with the corresponding normal tissue from the same patient. In a recent study, these paired samples were also stained with a 15-PGDH-specific antibody, and the normal colon samples showed significantly higher 15-PGDH protein expression compared to the matched colon cancer samples [21]. These findings are in good agreement with our mRNA data.…”
Section: Resultssupporting
confidence: 90%
“…According to previous studies, HPGD has been reported to be a tumor suppressor gene in several types of cancer. [18][19][20] Here, we showed that 15-PGDH expression in PDAC cells is sup- 21,31,32 In fact, LPS-treated activated macrophages significantly increased CD163 expression.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, 15-PGDH, which degrades prostaglandin, has attracted attention, and inhibition of 15-PGDH caused PGE 2 accumulation and promoted tissue regeneration in mice by expanding the tissue stem cell fraction. 17 Although 15-PGDH is known to be a tumor suppressor in colon, lung, and breast cancers, [18][19][20] the relationship between 15-PGDH expression and PDAC progression is still unclear. Here, we elucidated the mechanism underlying regulation of 15-PGDH expression and the prognostic impact of 15-PGDH expression in PDAC.…”
mentioning
confidence: 99%
“…At the same time, it is known that WNT5A acts to suppress tumour formation in several cancer types . In colon cancer, it even induces differentiation of neoplastic cells . A previous study showed that WNT5A is downregulated in Wilms tumour .…”
Section: Discussionmentioning
confidence: 99%
“…WNT5A is a key effector molecule in nephrogenesis and is also integrated with Hippo signalling [29,35]. It also plays a role in tumorigenesis and has been used to enforce the differentiation of colon cancer cells [36]. WNT5A mRNA expression was higher in IRX5 −/− compared to IRX3 −/− cells ( Figure 5B), while WNT5A protein was expressed in all histological elements of WiT49-derived tumours irrespective of IRX3/5 status ( Figure 6A-F).…”
Section: Wnt5a Is a Likely Effector Of Nephrogenic Tubule Maturationmentioning
confidence: 99%